2014
DOI: 10.1136/bmjopen-2014-005216
|View full text |Cite
|
Sign up to set email alerts
|

Pilot investigation of the oxygen demands and metabolic cost of incremental shuttle walking and treadmill walking in patients with cardiovascular disease

Abstract: ObjectiveTo determine if the metabolic cost of the incremental shuttle-walking test protocol is the same as treadmill walking or predicted values of walking-speed equations.SettingPrimary care (community-based cardiac rehabilitation).ParticipantsEight Caucasian cardiac rehabilitation patients (7 males) with a mean age of 67±5.2 years.Primary and secondary outcome measuresOxygen consumption, metabolic power and energy cost of walking during treadmill and shuttle walking performed in a balanced order with 1 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
1
16
2
1
Order By: Relevance
“…In a previous study, subjects with cardiac disease demonstrated a poorer performance on a treadmill than in a hallway due to the greater energy expenditure required (3.22 Ϯ 0.55 J/kg/m vs 3.00 Ϯ 0.41 J/kg/m). 9 Our findings were different. A plausible explanation for this result is that all participants used the handrail for support, which demonstrates that this resource influences physiological responses, leading to better performance on the ISWT-T.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In a previous study, subjects with cardiac disease demonstrated a poorer performance on a treadmill than in a hallway due to the greater energy expenditure required (3.22 Ϯ 0.55 J/kg/m vs 3.00 Ϯ 0.41 J/kg/m). 9 Our findings were different. A plausible explanation for this result is that all participants used the handrail for support, which demonstrates that this resource influences physiological responses, leading to better performance on the ISWT-T.…”
Section: Discussioncontrasting
confidence: 66%
“…Compared to the ISWT-H, a substantial reduction in the walking distance has been demonstrated for the 6-min walk test, 4,5 the 12-min walk test, 6,7 and the ISWT 8 when performed on a treadmill, along with a higher energy cost per meter on the ISWT. 9 Indeed, there are important differences in gait mechanics between walking on a treadmill and walking in a hallway. 5,[9][10][11] A treadmill requires greater effort and energy to maintain lateral balance and is an activity with which many patients are not familiar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this analysis we undertook a pilot investigation to compare treadmill walking with more commonly used protocols involving shuttle-walking. [27] We found that the metabolic demands of treadmill walking were fundamentally different from shuttle-walking. On this basis, we excluded such data from the remaining eligible study.…”
Section: Inclusion Criteriamentioning
confidence: 84%
“…(ml·kg -1 ·min -1 or Metabolic Equivalents [METs]) but consensus is currently lacking regarding the most appropriate method of estimation [25][26][27].…”
Section: R2peakmentioning
confidence: 99%